Environment protection and its reflection in the environmental consciousness of the inhabitants in a middle-sized town (Vác, Hungary) - Megyeri-Runyó, Anna (Acta Geographica Debrecina Landscape & Environment series, 2010)
Abstract The paper presents the role of urban environmental protection in sustainable development while analysing the factors influencing the environmental consciousness of the inhabitants of a middle-sized town based on a general model, together with the role of environmental consciousness in solving environmental protection problems at settlement level. My particular research focused on characterising the environmental state of Vác, with a population of 35000 people, and on the knowledge and environmental consciousness of the inhabitants. In the course of the representative questionnaire survey, 439 people gave assessable answers. Questions were related to the most significant environmental problems (air pollution, water contamination, sewage treatment, waste management). Answers were compared to the real situation based on measurements. Results revealed that the knowledge of the inhabitants on local environmental problems is better than the national average. In certain relations (water contamination, sewage treatment), however, it is deficient, thus information transfer was studied separately as well. It can be stated that local governments should make greater efforts in order to inform inhabitants. Environmental attitude of the inhabitants can be regarded as good. Based on the general model, I analysed the tasks of the settlement to improve environmental consciousness in order to increase efficiency of urban environmental protection.